2022
DOI: 10.1155/2022/6120107
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Nonadherence to WHO’s Recommended Antenatal Care Visits among Women in Pastoral Community, Northeastern Ethiopia: A Community-Based Cross-Sectional Study

Abstract: Introduction. More than half of the pregnant women in Ethiopia do not receive the recommended number of antenatal care visits. In the Afar region, where women have limited access to healthcare services due to pastoral livelihood, evidence on noncompliance to the adequate number of antenatal care visits is scarce. Therefore, this study was intended to examine the level of nonadherence to the recommended antenatal care visits and its associated factors in the pastoral community of Northeast Ethiopia. Methods. A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…This explanation was also supported by the premise generated from the national survey; women who reside in pastoralist regions barely used the service as set against a woman who resided in city administration (6,29). On top of this, the utilization of the service was dependent on the husband's education status, community acceptance, availability of service, early marriage and access to media had a pivotal role in the uptake of the service in the pastoralist regions (54,111,117). Thus, the finding imply that coordinated and concerted effort is needed to improve community awareness among the pastoralist community through various means of communication.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This explanation was also supported by the premise generated from the national survey; women who reside in pastoralist regions barely used the service as set against a woman who resided in city administration (6,29). On top of this, the utilization of the service was dependent on the husband's education status, community acceptance, availability of service, early marriage and access to media had a pivotal role in the uptake of the service in the pastoralist regions (54,111,117). Thus, the finding imply that coordinated and concerted effort is needed to improve community awareness among the pastoralist community through various means of communication.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have been conducted to pinpoint factors that affect the utilization of ANC services in Ethiopia. However, most of these studies were limited to small geographical areas, which may have had little influence on policy development and change (54)(55)(56)(57)(58)(59)(60)(61)(62). Furthermore, several studies failed to adopt the relevant counting model and instead relied on conventional methods of analysis, which have limitations in providing sufficient detail on a pattern of multiple ANC visits (43,(63)(64)(65)(66)(67).…”
Section: Introductionmentioning
confidence: 99%
“…Pregnant women often have unique insights into the factors that positively influence their attendance and adherence to ANC appointments; [26] regarding antenatal care attendance and associated factors, several quantitative studies have been conducted and showed a number of barriers and what is needed to address for further studies.…”
Section: Introductionmentioning
confidence: 99%
“…In 2020, under-five mortality rates in The Gambia were 62.74 deaths per 1000 live birth (NaNA, 2019). Anemia affects 44 percent of women of reproductive age and 55.8% of children under five (Urmale Mare et al, 2022). Furthermore, over 20,000 confirmed malaria cases raised the risk of low birth weight and complications during pregnancy (Gitonga, 2019;Manjang, 2022;Ononokpono & Odimegwu, 2021).…”
Section: Introductionmentioning
confidence: 99%